The effect of phytobiotic with F. ulmaria extract on the clinical and hematological status of post-milk calves - A. A. Ivanovsky (Аграрная наука Евро-Северо-Востока)
The aim of the study was to investigate the effect of an experimental phytobiotic supplement on morphological and biochemical parameters of blood and live weight gain in post-milk calves. The subject of the study was a phytobiotic  conditionally called Fitostim-L, the main active ingredients of which were biologically active compounds of meadowsweet (F. ulmaria (L.) Maxim.) and probiotic microorganisms. The experiment was conducted for 30 days on black-and-white calves, starting from the age of 2.5 months. The animals were divided into experimental (Fitostim-L) and control (farm ration) groups of 10 heads each. The calves of the experimental group received Fitostim-L orally, at a rate of 5 grams per head per day, after dilution in milk. At the beginning and at the end of the experiment, blood was tested twice for biochemical and morphological parameters. Morbidity, survivability, and live weight gain were taken into account. By the end of the experiment, blood analysis of calves in the experimental group, compared to the control, showed an increase in erythrocytes by 9.7 %, hemoglobin – by 18.4 % (Р<0.05), total protein – by 13.1 %, total Ig – by 18.9 % (Р<0.05), globulins – by 15.8 %, albumins – by 10.8 % (Р<0.05), a decrease in ALT activity by 19.1 %, AST – by 38.2 % (P < 0.05) and urea concentration by 12.8 % (P < 0.05). The average daily live weight gain of calves after using Fitostim-L exceeded the same indicator in the control by 0.27 kg.No sick animals were recorded in the experimental group, survivability was 100 %.